Find the Slope and Y-Intercept (-6,0) , (6,-3)

Math
(-6,0) , (6,-3)
Find the value of the slope.
Tap for more steps…
Slope is equal to the change in y over the change in x, or rise over run.
m=change in ychange in x
The change in x is equal to the difference in x-coordinates (also called run), and the change in y is equal to the difference in y-coordinates (also called rise).
m=y2-y1x2-x1
Substitute in the values of x and y into the equation to find the slope.
m=-3-(0)6-(-6)
Simplify.
Tap for more steps…
Reduce the expression by cancelling the common factors.
Tap for more steps…
Cancel the common factor of -3-(0) and 6-(-6).
Tap for more steps…
Rewrite -3 as -1(3).
m=-1⋅3-(0)6-(-6)
Factor -1 out of -1(3)-(0).
m=-1(3+0)6-(-6)
Reorder terms.
m=-1(3+0)6-6⋅-1
Factor 3 out of -1(3+0).
m=3(-1(1+0))6-6⋅-1
Cancel the common factors.
Tap for more steps…
Factor 3 out of 6.
m=3(-1(1+0))3(2)-6⋅-1
Factor 3 out of -6⋅-1.
m=3(-1(1+0))3(2)+3(-2⋅-1)
Factor 3 out of 3(2)+3(-2⋅-1).
m=3(-1(1+0))3(2-2⋅-1)
Cancel the common factor.
m=3(-1(1+0))3(2-2⋅-1)
Rewrite the expression.
m=-1(1+0)2-2⋅-1
m=-1(1+0)2-2⋅-1
m=-1(1+0)2-2⋅-1
Add 1 and 0.
m=-1⋅12-2⋅-1
m=-1⋅12-2⋅-1
Simplify the denominator.
Tap for more steps…
Multiply -2 by -1.
m=-1⋅12+2
Add 2 and 2.
m=-1⋅14
m=-1⋅14
Simplify the expression.
Tap for more steps…
Multiply -1 by 1.
m=-14
Move the negative in front of the fraction.
m=-14
m=-14
m=-14
m=-14
Find the value of the y-intercept.
Tap for more steps…
Substitute the value of m into the slope-intercept form of the equation, y=mx+b.
y=(-14)⋅x+b
Substitute the value of x into the slope-intercept form of the equation, y=mx+b.
y=(-14)⋅(-6)+b
Substitute the value of y into the slope-intercept form of the equation, y=mx+b.
0=(-14)⋅(-6)+b
Rewrite the equation as (-14)⋅(-6)+b=0.
(-14)⋅(-6)+b=0
Simplify each term.
Tap for more steps…
Cancel the common factor of 2.
Tap for more steps…
Move the leading negative in -14 into the numerator.
-14⋅-6+b=0
Factor 2 out of 4.
-12(2)⋅-6+b=0
Factor 2 out of -6.
-12⋅2⋅(2⋅-3)+b=0
Cancel the common factor.
-12⋅2⋅(2⋅-3)+b=0
Rewrite the expression.
-12⋅-3+b=0
-12⋅-3+b=0
Combine -12 and -3.
–32+b=0
Multiply -1 by -3.
32+b=0
32+b=0
Subtract 32 from both sides of the equation.
b=-32
b=-32
The values of the slope and y-intercept are m=-14 and b=-32.
m=-14
b=-32
Find the Slope and Y-Intercept (-6,0) , (6,-3)

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top